Gastric Bypass Promotes More Lipid Mobilization Than a Similar Weight Loss Induced by Low-Calorie Diet. (14th October 2010) - Kullberg, Joel; Sundbom, Magnus; Haenni, Arvo; Freden, Susanne; Johansson, Lars; Börnert, Peter; Ahlström, Anders; Ahlström, Håkan; Karlsson, Anders
Abstract : Background . Recently, we found large reductions in visceral and subcutaneous fat one month after gastric bypass (GBP), without any change in liver fat content. Purpose . Firstly to characterize weight loss-induced lipid mobilization after one month with preoperative low-calorie diet (LCD) and a subsequent month following GBP, and secondly, to discuss the observations with reference to our previous published findings after GBP intervention alone. Methods . 15 morbidly obese women were studied prior to LCD, at GBP, and one month after GBP. Effects on metabolism were measured by magnetic resonance techniques and blood tests. Results . Body weight was similarly reduced after both months (mean: −8.0 kg, n = 13 ). Relative body fat changes were smaller after LCD than after GBP (− 7.1 ± 3.6 % versus − 10 ± 3.2 %, P = .029, n = 13 ). Liver fat fell during the LCD month (−41%, P = .001, n = 13 ) but was unaltered one month after GBP (+12%). Conclusion . Gastric bypass seems to cause a greater lipid mobilization than a comparable LCD-induced weight loss. One may speculate that GBP-altered gastrointestinal signalling sensitizes adipose tissue to lipolysis, promoting the changes observed.